The determinant of export price in Malaysia / Muhammad Firdaus Mat Youb - Mat Youb, Muhammad Firdaus (Faculty of Business and Management, 2017)
The aim of this study is to examine determinant of export price in Malaysia. This paper examines whether the changes trend of the export price in Malaysia will give an impact on gross domestic product, foreign direct investment and exchange rate. Over the past few years, the export price in Malaysia has experienced difficulty after economic crisis. The study will explain more about the relationship between the export price and the independent variables for 30 years. In the process of findings there are few types of analysis were tested using Econometric Views (E-views), such as single linear regression, multiple linear regression, descriptive statistics, unit root tests, and more. The result indicates that there are significantly related to economic growths. This study can be useful for investors, companies and even government to know which factors that affect economy in Malaysia.